THE THEORETICAL FEASIBILITY OF PREZI SLIDE MEDIA IN HUMAN BLOOD CIRCULATION SYSTEM - ROSADI, HENDRA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
Human circulatory system is abstract material and beyond the day-to-day experience of students. One effort to overcome this problem is to create a Prezi slide media. This research was conducted to produce slide media based on Prezi application program on human circulatory system and describe the theoretical feasibility based on the experts. This research consisted of five development step, identification, enrichment, preparation, frame setting, validation, and revision. The instrument to assess theoretical feasibility was a validation sheet of slide media based on Prezi application program. The research result showed that Prezi slide media got value about 92,50%, It meant that Prezi slide media developed was worthy theoretically. Key words: slide media, prezi, human circulatory system.